Holographic Dark Energy with Extended Chaplygin Gas Model. Issue 2 (3rd July 2019) - Khadekar, G.S.; Gupta, Aina
Abstract: In this paper we consider a correspondence between holographic dark energy density and extended Chaplygin gas energy density proposed by Pourhassan and Kahya [2014] (Advances in High Energy Physics, 231452, 2014) in FRW universe. We solve the Friedmann equation and investigate the be- haviour of cosmological parameters and also we reconstruct the potential and dynamics of the scalar field which describe the extended Chaplygin gas cosmology.